Ivabradine in Heart Failure: The Representativeness of SHIFT (Systolic Heart Failure Treatment With the IF Inhibitor Ivabradine Trial) in a Broad Population of Patients With Chronic Heart Failure. (September 2017) - Das, Debraj; Savarese, Gianluigi; Dahlström, Ulf; Fu, Michael; Howlett, Jonathan; Ezekowitz, Justin A.; Lund, Lars H.
Abstract : Background: The sinus node inhibitor ivabradine was approved for patients with heart failure (HF) after the ivabradine and outcomes in chronic HF (SHIFT [Systolic Heart Failure Treatment With the IF Inhibitor Ivabradine Trial]) trial. Our objective was to characterize the proportion of patients with HF eligible for ivabradine and the representativeness of the SHIFT trial enrollees compared with those in the Swedish Heart Failure Registry. Methods and Results: We examined 26 404 patients with clinical HF from the Swedish Heart Failure Registry and divided them into SHIFT type (left ventricular ejection fraction <40%, New York Heart Association class II–IV, sinus rhythm, and heart rate ≥70 beats per minute) and non-SHIFT type. Baseline characteristics and medication use were compared and change in eligibility over time was reported at 6 months and 1 year in a subset of patients. Overall, 14.2% (n=3741) of patients were SHIFT type. These patients were more likely to be younger, men, have diabetes mellitus, ischemic heart disease, lower left ventricular ejection fraction, and more recent onset HF (<6 months; all, P <0.001). Although 88.9% of SHIFT type and 88.5% of non-SHIFT type ( P =0.421) were receiving selected β-blockers, only 58.8% and 67.3% ( P <0.001) were on >50% of target dose. From those patients who had repeated visits within 6 months (n=5420) and 1 year (n=6840), respectively, 10.2% (n=555) and 10.6% (n=724) of SHIFT-type patients became ineligible, 77.3% (n=4188) and 77.3% (n=5287) remained ineligible, and 4.6% (n=252) and 4.9% (n=335) of non-SHIFT–type patients became eligible for initiation of ivabradine. Conclusions: From the Swedish Heart Failure Registry, 14.2% of patients with HF were eligible for ivabradine. These patients more commonly were not receiving target β-blocker dose. Over time, a minority of patients became ineligible and an even smaller minority became eligible. Abstract : Supplemental Digital Content is available in the text.